EKSISTENSI PENDIDIKAN PESANTREN DALAM SISTEM PENDIDIKAN NASIONAL BERDASARKAN UNDANG-UNDANG PESANTREN - Zibbat, Muhammad; Hariri, Ahmad (Universitas Islam Madura, 2024)
Islamic boarding school education currently has a very high role and sympathy among society, because it is considered to have advantages compared to other formal educational institutions, but from the other side, researchers are curious about how the Islamic boarding school law positions it within the scope of education and as a form of state recognition of its presence. Islamic boarding schools in the world of education. The research method used is a qualitative approach with a literature review type. Data sources are reference books, journals and several sources that are related to the research theme. The research results show that recognition of Islamic boarding school education refers to providing freedom to develop the curriculum, teaching methods typical of Islamic boarding school education, and recognition in terms of awarding diplomas which are recognized as the same as formal education. The implications of this research are: 1) strengthening Islamic boarding school education in the national education system, 2) improving the quality of Islamic boarding school education, 3) developing Islamic boarding school-based curriculum, 4) empowering Islamic boarding school management, 5) recognizing the implementation of alternative education, 6) strengthening Islamic boarding school education, 7) development of inclusive education, 8) collaboration in Islamic boarding school education and other institutions. Some of these implications can be used as views for other researchers and policy holders in formulating education policies.